Rapid tumor vaccine using Toll-like receptor-activated ovarian cancer ascites monocytes. Issue 2 (16th August 2020) - Adams, Sarah F; Grimm, Alizée J; Chiang, Cheryl L-L; Mookerjee, Ananda; Flies, Dallas; Jean, Stephanie; McCann, Georgia A; Michaux, Justine; Pak, HuiSong; Huber, Florian; Neal, Christopher; Dangaj, Denarda; et al.
Abstract : Background: Novel therapeutic strategies in ovarian cancer (OC) are needed as the survival rate remains dismally low. Although dendritic cell-based cancer vaccines are effective in eliciting therapeutic responses, their complex and costly manufacturing process hampers their full clinical utility outside specialized clinics. Here, we describe a novel approach of generating a rapid and effective cancer vaccine using ascites-derived monocytes for treating OC. Methods: Using the ID8 mouse ovarian tumor model and OC patient samples, we isolated ascites monocytes and evaluated them with flow cytometry, Luminex cytokine and chemokine array analysis, ex vivo cocultures with T cells, in vivo tumor challenge and T cell transfer experiments, RNA-sequencing and mass spectrometry. Results: We demonstrated the feasibility of isolating ascites monocytes and restoring their ability to function as bona fide antigen-presenting cells (APCs) with Toll-like receptor (TLR) 4 lipopolysaccharide and TLR9 CpG-oligonucleotides, and a blocking antibody to interleukin-10 receptor (IL-10R Ab) in the ID8 model. The ascites monocytes were laden with tumor antigens at a steady state in vivo. After a short 48 hours activation, they upregulated maturation markers (CD80, CD86 and MHC class I) and demonstrated strong ex vivo T cell stimulatory potential and effectively suppressed tumor and malignant ascites in vivo. They also induced protective long-term T cell memory responses. To evaluate the translational potential of this approach, we isolated ascites monocytes from stage III/IV chemotherapy-naïve OC patients. Similarly, the human ascites monocytes presented tumor-associated antigens (TAAs), including MUC1, ERBB2, mesothelin, MAGE, PRAME, GPC3, PMEL and TP53 at a steady state. After a 48-hour treatment with TLR4 and IL-10R Ab, they efficiently stimulated oligoclonal tumor-associated lymphocytes (TALs) with strong reactivity against TAAs. Importantly, the activated ascites monocytes retained their ability to activate TALs in the presence of ascitic fluid. Conclusions: Ascites monocytes are naturally loaded with tumor antigen and can perform as potent APCs following short ex vivo activation. This novel ascites APC vaccine can be rapidly prepared in 48 hours with a straightforward and affordable manufacturing process, and would be an attractive therapeutic vaccine for OC.